2020
DOI: 10.2147/ott.s261068
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pretreatment CT-Based Radiomics Signature as a Potential Imaging Biomarker for Predicting the Expression of PD-L1 and CD8+TILs in ESCC</p>

Abstract: Background: The present study constructed and validated models to predict PD-L1 and CD8+TILs expression levels in esophageal squamous cell carcinoma (ESCC) patients using radiomics features and clinical factors. Patients and Methods: This retrospective study randomly assigned 220 ESCC patients to a discovery dataset (n= 160) and validation dataset (n= 60). A total of 462 radiomics features were extracted from the segmentation of regions of interest (ROIs) based on pretreatment CT images of each patient. The LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Preoperatively assessing the immune status of patients ca cians to identify which patients are suitable for immunotherapy, thereb ment efficiency and overall survival rate. The expression level of PD portant role in guiding the selection of ICI therapy for liver cancer patie of radiomics features for preoperatively assessing PD-L1 expression has attracted significant attention in the literature [46][47][48][49][50][51]. For example combined quantitative and qualitative radiomics features to preoperati pression of PD-L1 biomarker in resected HCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preoperatively assessing the immune status of patients ca cians to identify which patients are suitable for immunotherapy, thereb ment efficiency and overall survival rate. The expression level of PD portant role in guiding the selection of ICI therapy for liver cancer patie of radiomics features for preoperatively assessing PD-L1 expression has attracted significant attention in the literature [46][47][48][49][50][51]. For example combined quantitative and qualitative radiomics features to preoperati pression of PD-L1 biomarker in resected HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of PD-L1 plays an important role in guiding the selection of ICI therapy for liver cancer patients. The utilization of radiomics features for preoperatively assessing PD-L1 expression before ICI therapy has attracted significant attention in the literature [46][47][48][49][50][51]. For example, Hectors et al [46] combined quantitative and qualitative radiomics features to preoperatively assess the expression of PD-L1 biomarker in resected HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT radiomics features have also been successfully used to identify programmed death-ligand 1 and CD8+ tumor infiltrating lymphocyte expression levels in patients with ESCC. Such analyses, performed on pretreatment CT images, allowed for better patient stratification and selection of candidates for immune checkpoint inhibitor therapy[ 21 ]. Finally, other encouraging applications of CT radiomics analysis in ESCC are pretreatment local staging[ 22 ] and assessment of lymph node status[ 23 , 24 ] with advantage over morphological features and size criteria.…”
Section: Applications Of Ai In Gi Radiologymentioning
confidence: 99%
“…They may extract spatial and temporal features from images that are useful in predicting the underlying molecular mechanisms, the tumor-immune microenvironment, and clinical outcome. Studies dealing with glioma, esophagus, lung, and liver cancers have shown that several imaging features extracted by radiomics were closely related to CD8 + TIL density (15)(16)(17)(18)(19). While reports are predicting clinicopathological results from tissue sections in PDAC (20)(21)(22), so far, there are no radiomic studies revealing the immune environment in PDAC.…”
Section: Introductionmentioning
confidence: 99%